PENGARUH PENGGUNAAN LKM TRIGONOMETRI BERBASIS PENEMUAN TERBIMBING TERHADAP HASIL BELAJAR - Denok Julianingsih (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2021)
The purpose of this study was to determine whether there was an effect of using Guided Discovery-based Trigonometry LKM on student learning outcomes in Trigonometry lectures even semester 2019/2020. This research is a quasi-experimental research with 8 students who teach trigonometry as a research subject. The design in this study used a one-group pretest-posttest design. The instrument used in this study was a test of learning outcomes consisting of pretest and posttest. The data analysis technique used was descriptive statistical analysis and inferential statistical analysis. The data were processed using SPSS 22. Based on the results of the descriptive analysis of student learning outcomes after the lecture using the Guided Discovery-based Trigonometry LKM was better than before using the Guided Discovery-based Trigonometry LKM. The average post-test learning outcome was 90.75 while the average learning outcome pretest of 28.75. As seen here there is an average increase of 62.00. While the results of inferential statistical analysis using the Wilcoxon Signed Rank Test obtained the value of Z count > Z table, namely -2.524 > -1.96, which means Ho is rejected and Ha is accepted. Meanwhile, based on the results of comparing the probability values, the Asymp value is obtained. Sig. (2-tailed) < the alpha value of 0.012 < 0.05 which means Ho is rejected and Ha is accepted. This means that there is a difference in the average results of students who use Guided Discovery-based Trigonometry LKM and students who do not use Guided Discovery-based Trigonometry LKM. That is, there is an effect of using Guided Discovery-based Trigonometry LKM on student learning outcomes.